Exogenous melatonin confers cold tolerance in rapeseed (Brassica napus L.) seedlings by improving antioxidants and genes expression. (31st December 2022) - Lei, Yan; He, Huang; Raza, Ali; Liu, Zeng; Xiaoyu, Ding; Guijuan, Wang; Yan, Lv; Yong, Cheng; Xiling, Zou
ABSTRACT: Rapeseed ( Brassica napus L.) is an important oilseed crop globally. However, its growth and production are significantly influenced by cold stress. To reveal the protective role of exogenous melatonin (MEL) in cold tolerance, rapeseed seedlings were pretreated with different concentrations of MEL before cold stress. The results indicated that the survival rate was increased significantly by the MEL pretreatment under cold stress. Seedlings pretreated with 0.01 g L −1 MEL were all survived and were used to analyze the physiological characteristics and the expression level of various genes related to cold tolerance. Under cold stress, exogenous MEL significantly increased the contents of proline, soluble sugar, and soluble protein; while the malondialdehyde content was decreased by exogenous MEL under cold stress. On the other hand, the activities of antioxidant defense enzymes such as catalase, peroxidase, and superoxide dismutase were also significantly enhanced. The results also showed that MEL treatment significantly upregulated the expression of Cu-SOD, COR6.6 ( cold-regulated), COR15, and CBFs ( C-repeat binding factor ) genes under cold stress. It was suggested exogenous MEL improved the content of osmotic regulatory substances to maintain the balance of cellular osmotic potential under cold stress and improved the scavenging capacity of reactive oxygen species by strengthening the activity of antioxidant enzymes and the cold-related genes expression.